PRELIMINARY STUDY OF THE ASSIMILATION CAPACITY OF SOYBEAN HULLS HYDROLYZATE BY RHODOTORULA MUCILAGINOSA CTC 7688 (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Microorganisms are today a consolidated source of value-added products. They can produce everything from lipids to antibiotics that are fundamental to human health. Yeasts, for example, have been studied for their ability to assimilate agroindustrial residues. The objective of this work was to study the ability of the yeast Rhodotorula mucilaginosa to assimilate a hydrolysate of soybean hulls for the production of lipids. Cultures were carried out on the main carbohydrates present in the hydrolysates of soybean hulls (arabinose, glucose and xylose) in order to verify the behavior of the yeast during the assimilation of each of these carbohydrates. During the cultivation the biomass concentration and the pH were evaluated. At the end of the culture, the lipid content was determined. The results showed that there was considerable biomass production when the hydrolysate was used (9.11 ±